Analisis pengaruh Return On Asset (ROA), Return On Equity (ROE), Earning Per Share (PER), dan Price Earning Ratio (PER) terhadap harga saham yang konsisten listing pada Jakarta Islamic Index (JII) - Muhammad Muhajir Aminy (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2019)
Purpose — This paper discusses the influence of the company's financial ratios, namely Return On Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), and Price Earning Ratio (PER) on stock price movements listed on Jakarta Islamic Index (JII).Research method — This study uses a quantitative approach with panel data regression analysis method with eight companies as samples.Result — This study found that all variables affect the movement of stock prices since in a simultaneous test with the value of Prob. F < alpha (0,05) and adjusted R-Squared value is 0,9709. While in partial test, EPS and PER are the only variables that have an impact on stock price movements. The variable that has a dominant influence on stock prices is EPS with a regression coefficient of 1,206877.